Analysis of cross-population differentiation between Thoroughbred and Jeju horses - Wonseok Lee; Kyung-Do Park; Mengistie Taye; Chul Lee; Heebal Kim; Hak-Kyo Lee; Donghyun Shin (Asian-Australasian Journal of Animal Sciences, 2018)
Objective This study was intended to identify genes positively selected in Thoroughbred horses (THBs) that potentially contribute to their running performances. Methods The genomes of THB and Jeju horses (JH, Korean native horse) were compared to identify genes positively selected in THB. We performed cross-population extended haplotype homozygosity (XP-EHH) and cross-population composite likelihood ratio test (XP-CLR) statistical methods for our analysis using whole genome resequencing data of 14 THB and 6 JH. Results We identified 98 (XP-EHH) and 200 (XP-CLR) genes that are under positive selection in THB. Gene enrichment analysis identified 72 gene ontology biological process (GO BP) terms. The genes and GO BP terms explained some of THB’s characteristics such as immunity, energy metabolism and eye size and function related to running performances. GO BP terms that play key roles in several cell signaling mechanisms, which affected ocular size and visual functions were identified. GO BP term Eye photoreceptor cell differentiation is among the terms annotated presumed to affect eye size. Conclusion Our analysis revealed some positively selected candidate genes in THB related to their racing performances. The genes detected are related to the immunity, ocular size and function, and energy metabolism.